The definitive guide to NetBeans Platform 7 - Bock, Heiko (Apress, 2011)
The NetBeans Platform is the world's only modular Swing application framework, used by very large organizations in mission-critical scenarios, such as at Boeing and Northrop Grumman, as well as in the financial sector and in the oil/gas industry. For these large customers in enterprises who are increasingly interested in Maven and OSGi, the book will have particular relevance. The Definitive Guide to NetBeans Platform 7 is a thorough and authoritative introduction to the open-source NetBeans Platform, covering all its major APIs in detail, with relevant code examples used throughout. Provides a completely updated definitive guide to the NetBeans Platform, using the latest APIs, coding patterns, and methodologies. Focuses strongly on business features in an application, since Oracle's customers are particularly interested in business-related aspects. For example, how to use OSGi, how to add authentication/security, how to monetize from a modular application. The original German book on which this title is based was well received. The NetBeans Platform Community has put together this English translation, which covers the latest NetBeans Platform 7 APIs. With an introduction by known NetBeans Platform experts Jaroslav Tulach and Tim Boudreau, this is the most up-to-date book on this topic at the moment. All NetBeans Platform developers will gain something from this book, because several topics in the book have not been documented anywhere else.